Late‐News Paper: The Biprimary Color System for E‐Paper: Doubling Color Performance Compared to RGBW. Issue 1 (June 2014) - Mukherjee, Sayantika; Heikenfeld, Jason; Smith, Nathan; Goulding, Mark; Topping, Claire; Norman, Sarah; Liu, Qin; Kramer, Laura
Abstract We demonstrate the "biprimary" color system with dual particle electrophoretic dispersions and a 3‐electrode system. Preliminary contrast ratios reach 10:1. Furthermore an electrokinetic cell is demonstrated confirming basic functionality for EKD panels. A theoretical pixel simulation confirms biprimary doubles the color performance compared to RGBW pixels.